Clinical importance of fibulin-5 immunohistochemical staining in breast lesions - Karanis, Meryem; Koksal, Hande; Ates, Emet; Dogru, Osman (Polish Journal of Pathology, 2019)
The aim of this study was to evaluate the clinical importance of fibulin-5, which has been shown to display tumour-promoting and tumour-protective functions in breast lesions. Sixty-two breast cancer patients, 19 patients with fibroadenoma, and 15 healthy breast tissues were enrolled. Forty-seven patients had invasive ductal carcinoma (IDC) (12 of them also had in situ carcinoma DCIS), and 15 had invasive lobular carcinoma (ILC). A scoring system from 0 to 4 was used to evaluate the fibulin-5 staining according to the percentage of stained cells. The median values of fibulin-5 staining scores of the breast cancer, fibroadenoma, and healthy breast tissues were 2 (range: 0-4), 3 (range: 3-4), and 4 (range: 1-4), respectively, and the difference is statistically significant (p = 0.0001). There was no significant difference between the fibulin-5 scores of IDC, ILC, and DCIS. Fifteen patients with triple-negative breast cancer (TNBC) had the lowest fibulin-5 score (p < 0.0001). The median fibulin-5 scores of the patients according to Ki-67 index ≥ 14% and < 14% were 2 (range: 1-5) and 4 (range: 1-5), respectively, and the difference is statistically significant (p = 0.001). These data can be explained by the inhibitory effect of fibulin-5 on epithelial cell proliferation, which is closely related to differentiation and prognosis.